Adsorption desalination : an emerging low-cost thermal desalination method - Ng, Kim Choon (2013)
Desalination, other than the natural water cycle, is hailed as the panacea to alleviate the problems of fresh water shortage in many water stressed countries. However, the main drawback of conventional desalination methods is that they are energy intensive. In many instances, they consumed electricity, chemicals for pre- and post-treatment of water. For each kWh of energy consumed, there is an unavoidable emission of Carbon Dioxide (CO2) at the power stations as well as the discharge of chemically-laden brine into the environment. Thus, there is a motivation to find new direction or methods of desalination that consumed less chemicals, thermal energy and electricity.